BS EN IEC 61937-15. Digital audio. Interface for non-linear PCM encoded audio bitstreams applying IEC 60958. Part 15. Non-linear PCM bit streams according to Auro-Cx format (TA 20) (15th November 2019) - British Standards Institution,
No abstract available